De novo mutations in TOMM70, a receptor of the mitochondrial import translocase, cause neurological impairment. (30th April 2020) - Dutta, Debdeep; Briere, Lauren C; Kanca, Oguz; Marcogliese, Paul C; Walker, Melissa A; High, Frances A; Vanderver, Adeline; Krier, Joel; Carmichael, Nikkola; Callahan, Christine; Taft, Ryan J; Simons, Cas; et al.
Abstract: The translocase of outer mitochondrial membrane (TOMM) complex is the entry gate for virtually all mitochondrial proteins and is essential to build the mitochondrial proteome. TOMM70 is a receptor that assists mainly in mitochondrial protein import. Here, we report two individuals with de novo variants in the C-terminal region of TOMM70. While both individuals exhibited shared symptoms including hypotonia, hyper-reflexia, ataxia, dystonia and significant white matter abnormalities, there were differences between the two individuals, most prominently the age of symptom onset. Both individuals were undiagnosed despite extensive genetics workups. Individual 1 was found to have a p.Thr607Ile variant while Individual 2 was found to have a p.Ile554Phe variant in TOMM70. To functionally assess both TOMM70 variants, we replaced the Drosophila Tom70 coding region with a Kozak-mini-GAL4 transgene using CRISPR-Cas9. Homozygous mutant animals die as pupae, but lethality is rescued by the mini-GAL4-driven expression of human UAS-TOMM70 cDNA. Both modeled variants lead to significantly less rescue indicating that they are loss-of-function alleles. Similarly, RNAi-mediated knockdown of Tom70 in the developing eye causes roughening and synaptic transmission defect, common findings in neurodegenerative and mitochondrial disorders. These phenotypes were rescued by the reference, but not the variants, of TOMM70 . Altogether, our data indicate that de novo loss-of-function variants in TOMM70 result in variable white matter disease and neurological phenotypes in affected individuals.